EFL Learners’ Vocabulary Achievement and Autonomy: Using Memrise Mobile Application - Zahra Zohoorian; Masoud Noorbakhsh; Mitra Zeraatpisheh (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
There has been rapid advancement in the use of technology through which an extensive array of mobile technologies have been introduced to educational contexts. In the same vein, mobile assisted language learning provides new possibilities for improving language learning conditions. The current study was an attempt to find out the effect of Memrise Mobile Application on Iranian upper-Intermediate EFL learners’ vocabulary achievement and their autonomy. To find the effects, a pre-test post-test quasi-experimental study was conducted. Fifty participants were selected from a cluster of 110 students. The Quick placement test as a test of homogeneity was administered to select the upper intermediate learners. Accordingly, 25 participants for each of the experimental and control groups were selected. Memrise Mobile Application was employed during the treatment period for teaching the 504 Absolutely Essential Words book to the experimental group while the control group was instructed the textbook of 504 Absolutely Essential Words. The intervention continued for a period of 8 weeks. A researcher-made vocabulary test and Zhang and Li’s (2004) standardized questionnaire on autonomy were administered. For the qualitative data collection, a semi-structured interview was conducted to determine the participants’ attitudes. An Independent T-test was run the results of which revealed a significant difference between the two groups in vocabulary achievement. However, there was no significant difference between the two groups in autonomy. Moreover, based on the qualitative data it was concluded that the experimental group participants were more motivated holding a more positive attitude.